FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PBB PADA EKS KARESIDENAN JAWA TENGAH (Students' Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of the independent variables, which consists of the Total Population, GDP and Inflation Rate for UN admission. The sampling technique used in this study was purposive sampling. Sampling was conducted in Kabupten Demak, Grobokan, Kendal, Semarang, Salatiga and Semarang in 2006-2011. This study uses multiple regression analysis because they use more than one independent variable. Based on the analysis it can be concluded that the independent variables Population, GDP and a significant positive influence on the acceptance of the United Nations, while the independent variables according to the inflation rate during the period of the study, the results showed that the rate of inflation is positive but not significant effect on acceptance of the UN.Keywords: Acceptance UN, Population, GDP and Inflation Rate.